1998
DOI: 10.1016/s0022-5223(98)70418-0
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of surface monocyte lipopolysaccharide-receptor cd14 in patients on cardiopulmonary bypass undergoing aorta-coronary bypass operation

Abstract: Cardiopulmonary bypass leads to reduced membrane-associated CD14 expression on peripheral blood monocytes and increased levels of soluble CD14 through shedding or secretion of membrane-associated CD14 from the cell surface. These findings indicate that bypass is associated with significant monocyte activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Only a transient downregulation of CD14 surface expression was observed. Decrease in CD14 expression on blood monocytes were reported in septicemic patients (42)(43)(44) and has been associated with apoptosis of monocytes (45) that was also observed in our culture conditions. This suggested that interaction with CHIKV did not lead to obvious monocytes activation.…”
Section: Discussionsupporting
confidence: 84%
“…Only a transient downregulation of CD14 surface expression was observed. Decrease in CD14 expression on blood monocytes were reported in septicemic patients (42)(43)(44) and has been associated with apoptosis of monocytes (45) that was also observed in our culture conditions. This suggested that interaction with CHIKV did not lead to obvious monocytes activation.…”
Section: Discussionsupporting
confidence: 84%
“…A decrease in monocyte count after initiation of CPB and monocytosis the morning after the CABG have been reported. 33,35 We observed a similar variation in our flow cytometry analyses (data not shown). This must be taken into account, evaluating the significance of monocyte surface receptor regulation.…”
Section: Discussionsupporting
confidence: 80%
“…However, monocyte CD14 expression after CABG is shown to be reduced the first postoperative day. 33 This downregulation of monocyte surface antigens probably represents a deactivation of monocytic proinflammatory functions, 34 and persistence of the deactivation may be associated with increasing risk of microbial invasion and infectious complications. We observed an initial downregulation of monocyte CD14, TLR-2, and TLR-4 after the CABG operation.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of the MHCII receptor was demonstrated in both on-bypass and OPCAB groups as previously described [6], whereas LPS receptor (CD14) expression only declined following on-bypass surgery. This drop in receptor expression may further potentiate immunoinflammatory resolution following cardiac surgery by reducing antigen presentation and endotoxin-mediated cytokine release, respectively [19]. Similar to CD163, monocyte CD14 is shed into the plasma during CPB surgery and minimises endotoxic effects by complexing with LPS [19].…”
Section: Discussionmentioning
confidence: 99%